1992
DOI: 10.1002/bjs.1800790919
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic prophylaxis in total hip replacement: A comparison between the low molecular weight heparinoid Lomoparan and heparindihydroergotamine

Abstract: In a prospective, randomized, assessor-blind multicentre study two antithrombotic subcutaneous regimens were compared in patients undergoing total hip replacement. Group 1 (154 patients) received 750 anti-Xa units of a new low molecular weight heparinoid (Lomoparan) subcutaneously twice a day and group 2 (155 patients) received 5000 units heparin and 0.5 mg dihydroergotamine (heparin-DHE 5000) twice a day. The incidence of deep vein thrombosis, assessed by routine bilateral venography on day 10 (+/- 1), was 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In patients who have had major hip or knee surgery low molecular weight heparins were significantly more effective than unfractionated heparin (5000 U subcutaneously two or three times a day) 17 18. Low molecular weight heparins were also more effective than adjusted dose unfractionated heparin,19 oral anticoagulants,20 21 dextran,22 23 and aspirin in such patients.…”
Section: Hospital Patients At High Riskmentioning
confidence: 96%
“…In patients who have had major hip or knee surgery low molecular weight heparins were significantly more effective than unfractionated heparin (5000 U subcutaneously two or three times a day) 17 18. Low molecular weight heparins were also more effective than adjusted dose unfractionated heparin,19 oral anticoagulants,20 21 dextran,22 23 and aspirin in such patients.…”
Section: Hospital Patients At High Riskmentioning
confidence: 96%
“…[24] The only study that directly compares low dose unfractionated heparin in combination with dihydroergotamine mesylate and danaparoid sodium showed that both regimens provided a similar degree of tolerability, as determined by blood losses and bleeding complications. [17] …”
Section: Bleeding Complicationsmentioning
confidence: 97%
“…A newly synthetized heparinoid, ORG 10172 (lomoparan), has proven to be beneficial in recent trials (11,36). However, data are still preliminary.…”
Section: Effective Measuresmentioning
confidence: 98%